Analisis Permintaan Buah Terong Analisis Permintaan Buah Terong Belanda (Solanum Betaceum) (Studi Kasus : Pasar Induk Kecamatan Medan Tuntungan) - Nasution, Suhela Putri; Abdurrozzaq Hasibuan (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
Dutch eggplant is a fresh fruit that is rich in health benefits. Apart from its delicious taste, tamarillo contains a variety of important nutrients, including vitamin C, antioxidants and fiber. The aim of this research is to determine the demand for Dutch eggplant (Solanum Betaceum) in the Medan Tuntungan District Main Market case study. The determination of respondents in this study was divided into 2 categories, namely tamarillo fruit traders and consumers who bought tamarillo fruit. For tamarillo fruit traders, all tamarillo fruit traders who were in the main market in Medan Tuntungan District were determined, while for tamarillo fruit consumers it was determined individually. The census numbered 25 people. The results of the research show that the factors that simultaneously influence the demand for tamarillo fruit in the main market are the price of tamarillo fruit, consumer income, and the price of other fruit for the number of dependents variable which does not influence the demand for tamarillo fruit in the main market at Medan Tuntungan subdistrict.